Adoption of Brain-Based Instruction by Higher Education Science and Engineering Departments in Ethiopia: A Quantitative and Qualitative Survey - Ataklti Abraha; Luo Siming (European Scientific Journal, ESJ, 2021)
Brain-Based Instruction methods have become influential at almost all educational levels. This paper examined the extent to which Natural and Computational Sciences and Engineering instructors in Ethiopian Higher Education Institutions apply Brain-Based Instruction principles (i.e., relaxed alertness, orchestrated immersion, and active processing) in their learningteaching process. This paper used a descriptive survey research design with a concurrent mixed (quantitative and qualitative) methodology. A questionnaire was used to gather quantitative data from a random sample of 512 instructors (292 from Natural and Computational Sciences and 220 from Engineering). Qualitative data were gathered from six selected instructors (three from Natural and Computational Sciences and three from Engineering) via a semistructured interview. A pilot study was used to confirm the validity and reliability of the research instruments. Quantitative data were analyzed by standard univariate methods. Qualitative data were analyzed by thematic analysis. The findings depicted that limited implementation of Brain-Based Instruction principles. Furthermore, the study showed that Higher Diploma Program training and length of teaching experience positively influenced the use of Brain-Based Instruction principles. The paper discusses implications for Brain-Based Instruction in Ethiopia and suggests areas for future research.